(untitled) (Journal of Science Foundation, 2013)
Ten cows, each of native (local cow) and crossbred (local × crossbred) origins differing in lactation yield were used in 2×2×2×2 factorial experiment using RBD to evaluate existing milk urea nitrogen (MUN) of cows considering regions and seasons. The live weight and BCS of cows under good feed base management condition was higher than of the poor feed base management condition. Feed intake of cows under good and feed base management condition was significantly (P<0.01) higher than of the intake of cows under poor feed base condition. Daily dry matter intake (DMI) of cows under good and poor feed base condition was 8.53 and 5.40 kg, respectively. Daily ME intake of cows under good and poor feed base management condition were 70.23 and 40.20 MJ, respectively. The requirements of ME (ARC, 1994) were 83.3 and 51.7 MJ, respectively. The intake of CP, RDP and UDP were 839.0, 488.5 and 350.9 g/d, respectively in good feed base and 386.0, 166.0 and 220.0 g/d, respectively in poor feed base region. The daily protein intake as live weight and milk production in good and poor feed base management condition were significantly (P<0.01) lower (-270.0 and -164.5 g, respectively) than the requirement (ARC, 1994). The daily RDP intake were significantly (P<0.01) lower than the requirement (ARC, 1994). Daily milk yield and 4% FCM of cows under good feed base condition were 6.76 and 6.49 kg, respectively and under poor feed base condition were 3.67 and 3.31 kg, respectively, which differed significantly (P<0.01). The milk protein, lactose, SNF, minerals and total solids under good feed base condition were 3.79, 5.49, 10.09, 0.63 and 14.06%, respectively and under poor feed base condition were 3.63, 5.29, 9.80, 0.61 and 13.52, respectively, which were significantly (P<0.01) influenced by feed base. MUN and BUN under good feed base condition were found 38.86 and 40.98 mg/dl, respectively and under poor feed base condition 28.55 and 33.13 mg/dl, respectively, and this difference between the two areas were statistically significant (P<0.01). The live weight of cow was 284.0 kg in the dry season and in the winter season 282.3 kg which did not differ significantly (P>0.05). Intake of CP and RDP in dry season was found 664 and 358.5 g/d, respectively and in the wet season it was 561 and 296 g/d, respectively, which differed significantly (P<0.01). BUN and MUN in dry season were 37.35 and 36.79 mg/dl, respectively and in wet season 36.75 and 36.87 mg/dl, respectively. The live weight and BCS of crossbred cows was higher than that of the local cows. The live weight and BCS of crossbred cow were 318.8 kg & 2.85, respectively and of local cow were 247.5 kg & 2.34, respectively, which was significantly (P<0.01) higher than local cow. The daily DMI of local cow was 5.75 kg and crossbred cow was 8.17 kg, which differed significantly (P<0.01). Daily ME intake of crossbred cow (64.82 MJ) was significantly (P<0.01) higher than local cow (45.60 MJ), which were lowered compared to the requirement as per ARC (1994). Daily CP, RDP and UDP intake of crossbred cow were 708, 378 and 330 g, respectively and of local cow were 517, 276 and 240 g, respectively; which differed significantly (P<0.01). Daily milk yield and 4%FCM of local cows were 3.26 and 3.28 kg, respectively and of crossbred cows were 7.18 and 6.52 kg, respectively, which differed significantly (P<0.01). The milk protein of local cow was 3.73 % and of crossbred was 3.70 %, which differed significantly (P<0.01). The MUN and BUN of the local cow were 31.97 and 34.94 mg/dl, respectively and of crossbred cows were 35.44 and 39.17 mg/dl, respectively, which were statistically significant (P<0.01). It may be concluded that the MUN depends on plane of nutrition of cows, seasons and their genotypes but stages of lactation may not be affect its level in milk. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14632 J. Sci. Foundation, 8(1&2): 97-110, June-December 2010